The concept of polis religion: content, historical-religious argumentation, criticism - Pavlov, Nikita Mikhailovich (Исторический журнал: научные исследования, 2024)
This article is devoted to a review analysis of the theory of polis religion in relation to ancient Greek culture. The article examines both arguments supporting this concept and critical opinions questioning it. The subject of the study is the concept of polis religion, the object is historio-graphical literature dealing with the comprehension and formation of ideas about the concept. In the first section you can find a review of the arguments in favor of polis religion, the work of leading experts in the field of ancient history and the history of religion involved in the analysis. The key theses that substantiate the existence and importance of the polis religion for the life of the city-states of Ancient Greece (polis) are highlighted. The role of religion in the political life of the Greek policy is discussed, as well as its influence of religious institutions on social structures. In the second section, the focus shifts to criticism of the concept of polis religion. The works of historians who question the universality and unambiguity of this theory are presented. Critics point to the diversity of religious practices and beliefs in different policies, the presence of individual cults and personal religious beliefs that do not always meet policy standards. The final section summarizes the results of the study. In this part of the article, the author seeks to offer a balanced view of polis religion, recognizing both the importance of this concept and the limitations of its use. A consensus point of view is formulated, which takes into account both supporters and critics of this concept. The scientific consensus on the theory at the moment can be formulated as follows: the concept of polis religion can be preserved only in its weak formulation.